Investigation of New Ion Conducting Ormolytes Silica-Polypropyleneglycol - Dahmouche, K. [UNESP]; De Souza, P. H.; Bonagamba, T. J.; Paneppucci, H.; Judeinstein, P.; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Springer Nature, 1999)
Two groups of hybrid organic-inorganic composites exhibiting ionic conduction properties, so called ORMOLYTES (organically modified electrolytes), have been prepared by the sol-gel process. The first group has been prepared from mixture of a lithium salt and 3-isocyanatopropyltriethoxysilane(IsoTrEOS),O,O′-bis(2-aminopropyl) polypropyleneglycol. These materials produce chemical bonds between the organic (polymer) and the inorganic (silica) phases. The second group has been prepared by an ultrasonic method from a mixture of tetraethoxysilane (TEOS), polypropyleneglycol and a lithium salt. The organic and inorganic phases are not chemically bonded in these samples. The Li+ ionic conductivity, σ, of all these materials has been studied by AC impedance spectroscopy up to 100°C. Values of σ up to 10-6 Ω-1·cm-1 have been found at room temperature. A systematic study of the effects of lithium concentration, polymer chain length and the polymer to silica weight ratio on σ shows that there is a strong dependence of σ on the preparation conditions. The dynamic properties of the Li+ ion and the polymer chains as a function of temperature between -100 and 120°C were studied using 7Li solid-state NMR measurements. The ionic conductivity of both families are compared and particular attention is paid to the nature of the bonds between the organic and inorganic components.
Keywords: Hybrid material; Ionic conductor; Silica-polypropyleneglycol; Solid electrolyte; Chemical bonds; Ionic conduction in solids; Lithium; Nuclear magnetic resonance; Polyethers; Silica; Sol-gels; Solid electrolytes; Spectroscopic analysis; Concentration (process); Inorganic compounds; Ionic conduction; Organic compounds; Polymers; Thermal effects; Organically modified electrolytes; Polypropylene glycols; Hybrid materials; Ionic conductors; Lithium salts; Polyelectrolytes; Ions